Ethylene Glycol Slurry

JP7631798B2Active Publication Date: 2025-02-19MITSUBISHI CHEM CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020217116
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-25
Publication Date
2025-02-19
Estimated Expiration
2040-12-25

AI Technical Summary

Benefits of technology

【0012】 本発明によれば、高温保管時の粘度上昇を抑えた、保存安定性に優れた有機架橋高分子粒子含有エチレングリコールスラリーを提供することができる。 本発明によれば、このエチレングリコールスラリーを用いて、ポリエチレンテレフタレート製造時の任意の段階で有機架橋高分子粒子含有エチレングリコールスラリーを円滑に添加して、透明性、取り扱い性に優れたポリエチレンテレフタレート、更にはポリエチレンテレフタレートフィルムを製造することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007631798000001
    Figure 0007631798000001
Patent Text Reader

Abstract

To provide an organic crosslinked polymer particle-containing ethylene glycol slurry with excellent storage stability that can suppress the increase in viscosity even during high-temperature storage.SOLUTION: Provided are: an ethylene glycol slurry that contains an organic crosslinked polymer particle, a surfactant, aspartic acid and ethylene glycol; a method for producing polyethylene terephthalate that comprises a step of adding the ethylene glycol slurry; and a method for producing polyethylene terephthalate film by forming polyethylene terephthalate produced by the method for producing polyethylene terephthalate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an ethylene glycol slurry containing organic crosslinked polymer particles that has excellent stability during high-temperature storage, a method for producing polyethylene terephthalate using the ethylene glycol slurry, and a method for producing a polyethylene terephthalate film. [Background technology]

[0002] Polyester films, particularly polyethylene terephthalate and polyethylene naphthalate films, have excellent transparency, mechanical properties, heat resistance, and chemical resistance, and therefore have been widely used in recent years, particularly in various optical films. For example, they are used in applications such as prism lens sheets, touch panels, and backlights, which are components of liquid crystal display devices, base films for anti-reflection films, electromagnetic shielding films for plasma displays, base films for organic EL displays, and explosion-proof base films for displays. The polyester films used in such optical films are required to have not only good appearance including transparency, but also improved workability when handling the film, that is, reduced friction coefficient and improved wear properties.

[0003] The reduction of the coefficient of friction and the improvement of the wear properties of the film can be achieved by blending inert fine particles with polyester. This method is roughly divided into a method of precipitating metal compound fine particles in the system during polycondensation and a method of adding inorganic or organic fine particles such as calcium carbonate, kaolin, silica, and organic crosslinked polymer from the outside. Among these, in order to obtain a polyester film with high transparency, an attempt has been made to disperse organic crosslinked polymer particles, which have a refractive index close to that of the raw material polyester and have relatively excellent affinity, in ethylene glycol, a raw material for polyester, to form a slurry, and to add this ethylene glycol slurry at any stage during the production of polyester (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2014-98136 A Summary of the Invention [Problem to be solved by the invention]

[0005] It has been found that the ethylene glycol slurry containing the organic crosslinked polymer particles described in Patent Document 1, specifically the crosslinked polymethyl methacrylate particles, increases in viscosity during high-temperature storage. When the viscosity of the ethylene glycol slurry increases, the ethylene glycol slurry containing the organic crosslinked polymer particles cannot be smoothly added, and in severe cases, the pipes are clogged, leading to the shutdown of the production facility.

[0006] An object of the present invention is to provide an ethylene glycol slurry containing organic crosslinked polymer particles, which is excellent in storage stability and in which an increase in viscosity can be suppressed even during storage at high temperatures. [Means for solving the problem]

[0007] As a result of extensive investigations aimed at solving the above problems, the present inventors discovered that by blending a surfactant and aspartic acid with an ethylene glycol slurry containing organic crosslinked polymer particles, an ethylene glycol slurry with excellent storage stability can be obtained in which the increase in viscosity during high-temperature storage is suppressed, and thus the present invention was completed.

[0008] That is, the present invention relates to the following.

[0009] [1] An ethylene glycol slurry comprising organic crosslinked polymer particles, a surfactant, aspartic acid and ethylene glycol.

[0010] [2] A method for producing polyethylene terephthalate, comprising the step of adding the ethylene glycol slurry described in [1].

[0011] [3] A method for producing a polyethylene terephthalate film, comprising molding polyethylene terephthalate produced by the method for producing polyethylene terephthalate according to [2]. Effect of the Invention

[0012] According to the present invention, it is possible to provide an ethylene glycol slurry containing organic crosslinked polymer particles, which is excellent in storage stability and in which an increase in viscosity during high-temperature storage is suppressed. According to the present invention, this ethylene glycol slurry can be used to smoothly add the ethylene glycol slurry containing organic crosslinked polymer particles at any stage during the production of polyethylene terephthalate, thereby producing polyethylene terephthalate and even polyethylene terephthalate films with excellent transparency and handleability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention will be described in detail below. However, the description of the constituent elements described below is one example (representative example) of an embodiment of the present invention, and the present invention is not limited to these contents.

[0014] [Ethylene glycol slurry] The ethylene glycol slurry of the present invention contains organic crosslinked polymer particles, a surfactant, aspartic acid and ethylene glycol.

[0015] <Organic crosslinked polymer particles> The organic crosslinked polymer particles used in the present invention are not limited in shape, composition, or production method, and organic crosslinked polymer particles of various shapes and compositions obtainable by various methods can be used.

[0016] A typical example of the composition of the organic crosslinked polymer particles used in the present invention is a copolymer of a vinyl compound (A) having one aliphatic unsaturated bond in the molecule and a compound (B) serving as a crosslinking agent having two or more aliphatic unsaturated bonds in the molecule. The organic crosslinked polymer particles used in the present invention must be substantially insoluble, infusible, and heat-resistant even at high temperatures during the production or molding of polyester. Specifically, it is desirable that the mass loss rate after heat treatment at 300°C for 30 minutes under a nitrogen gas flow is usually 30% by mass or less, particularly 20% by mass or less. For this reason, the organic crosslinked polymer particles used in the present invention preferably have a crosslinked structure, and are preferably a copolymer of the vinyl compound (A) and the compound (B).

[0017] Examples of the vinyl compound (A), which is one component of the copolymer, include acrylic acid, methacrylic acid, and their methyl or glycidyl esters, maleic anhydride and its alkyl derivatives, vinyl glycidyl ether, vinyl acetate, styrene, alkyl-substituted styrene, etc. Examples of the compound (B) include divinylbenzene, divinyl sulfone, ethylene glycol dimethacrylate, etc. One or more types of each of the vinyl compound (A) and the compound (B) can be used.

[0018] The crosslinking component such as divinylbenzene of compound (B) used in the production of the copolymer is preferably 5% by mass or more, for example 5 to 50% by mass, relative to 100% by mass of the total of compound (A) and compound (B), in order to prevent deformation and fusion of particles due to heating during polyester polymerization and heating during polyester film processing.

[0019] Typical examples of the organic crosslinked polymer particles used in the present invention include copolymers of methyl methacrylate and divinylbenzene, copolymers of methyl acrylate and divinylbenzene, copolymers of styrene and divinylbenzene, and copolymers of these systems further incorporating ethylene glycol units.

[0020] There is no particular limitation on the method for producing the organic crosslinked polymer particles used in the present invention, and any of suspension polymerization, emulsion polymerization, soap-free emulsion polymerization, etc. may be used. In this case, examples of the polymerization initiator that can be used include azobisisobutyronitrile, benzoyl peroxide, t-butyl peroxide, cumene hydroperoxide, hydrogen peroxide, potassium persulfate, potassium persulfate-sodium thiosulfate, etc.

[0021] The shape of the organic crosslinked polymer particles used in the present invention is not limited, and may be any shape such as spherical, spindle-shaped, or irregular.

[0022] In order to further increase the affinity with polyester, various functional groups can be introduced into the organic crosslinked polymer particles used in the present invention by surface treatment. Examples of functional groups include carboxyl groups, hydroxyl groups, amide groups, and sulfonic acid groups. The introduction of functional groups is preferably performed using methacrylic acid for carboxyl groups, acrylic monomers for hydroxyl groups, methacrylamide for amide groups, and styrene sulfonic acid for sulfonic acid groups, but is not limited thereto.

[0023] The volume average particle diameter of the organic crosslinked polymer particles used in the present invention is preferably 0.01 μm or more, more preferably 0.1 μm or more, and even more preferably 0.3 μm or more, when mixed with ethylene glycol to form a slurry. If the volume average particle diameter is equal to or more than the above lower limit, the running property and abrasion resistance can be sufficiently improved when the particles are formed into a polyester film. On the other hand, the volume average particle diameter of the organic crosslinked polymer particles used in the present invention is preferably 3 μm or less, more preferably 2.5 μm or less, and even more preferably 2.0 μm or less, when mixed with ethylene glycol slurry to form a slurry. If the volume average particle diameter is equal to or less than the above upper limit, the surface roughness of the polyester does not become too large, and the polyester film surface is prevented from being damaged and the transparency is prevented from being impaired.

[0024] In the present invention, the organic crosslinked polymer particles may be used alone or in combination of two or more types of copolymers differing in type, shape, particle size, etc.

[0025] <Surfactant> In the present invention, either a low molecular weight surfactant or a polymeric surfactant can be used as the surfactant, but from the viewpoints of good dispersibility and low toxicity, a polymeric surfactant is preferred. As for the type of surfactant, from the viewpoint of good dispersibility, anionic surfactants, nonionic surfactants, and cationic surfactants are preferred. As the surfactant, a commercially available surfactant can be appropriately selected and used. The surfactant may be used alone or in combination of two or more kinds.

[0026] <Content of each ingredient> The concentration (content) of the organic crosslinked polymer particles in the ethylene glycol slurry of the present invention is preferably 3% by mass or more, more preferably 5% by mass or more, and particularly preferably 10% by mass or more. If the concentration is equal to or more than the above lower limit, the amount of ethylene glycol slurry when adding the required amount of organic crosslinked polymer particles is not large, and large-scale equipment is not required. On the other hand, the concentration of the organic crosslinked polymer particles in the ethylene glycol slurry of the present invention is preferably 30% by mass or less, more preferably 25% by mass or less, and particularly preferably 20% by mass or less. If the concentration is equal to or less than the above upper limit, the increase in the viscosity of the ethylene glycol slurry is suppressed, and the handling during addition is good.

[0027] The concentration (content) of the surfactant in the ethylene glycol slurry of the present invention is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and particularly preferably 0.3% by mass or more. If the concentration is equal to or more than the above lower limit, the effect of improving dispersibility due to the addition of the surfactant can be sufficiently obtained. On the other hand, the concentration of the surfactant in the ethylene glycol slurry of the present invention is preferably 10% by mass or less, more preferably 5% by mass or less, and particularly preferably 3% by mass or less. If the concentration is equal to or less than the above upper limit, foaming during polyester polymerization can be suppressed.

[0028] The concentration (content) of aspartic acid in the ethylene glycol slurry of the present invention is preferably 1 mass ppm or more, more preferably 5 mass ppm or more, and particularly preferably 10 mass ppm or more. If the concentration is equal to or more than the above lower limit, the increase in viscosity during high-temperature storage due to the inclusion of aspartic acid can be sufficiently suppressed, and problems such as pipe clogging during polyester production can be reliably prevented. On the other hand, the concentration of aspartic acid in the ethylene glycol slurry of the present invention is preferably 100 mass ppm or less, more preferably 50 mass ppm or less, and particularly preferably 30 mass ppm or less. If the concentration is equal to or less than the above upper limit, the decrease in color tone of the polyester and polyester film obtained by adding the ethylene glycol slurry of the present invention can be suppressed.

[0029] The ethylene glycol slurry of the present invention preferably consists essentially of ethylene glycol, other than the organic crosslinked polymer particles, surfactant, and aspartic acid. Here, "consisting essentially of ethylene glycol" means that 90% by mass or more of the remainder other than the organic crosslinked polymer particles, surfactant, and aspartic acid is ethylene glycol, more preferably 95 to 100% by mass of the remainder, and particularly preferably 100% by mass of the remainder is ethylene glycol.

[0030] <Method of preparing ethylene glycol slurry> The method for preparing the ethylene glycol slurry of the present invention is not particularly limited, and may be, for example, a general method in which ethylene glycol is stirred using a stirring blade equipped with a motor, and a predetermined amount of organic crosslinked polymer particles, a surfactant, and aspartic acid are added and mixed therein. If necessary, pretreatment such as pulverization, classification, and filtration can also be performed. Incidentally, aspartic acid may be added by being contained in the surfactant.

[0031] <Viscosity of ethylene glycol slurry> The viscosity of the ethylene glycol slurry of the present invention is preferably 150 mPa·s or less, more preferably 100 mPa·s or less, and even more preferably 70 mPa·s or less. If the viscosity exceeds 150 mPa·s, there is a risk of the piping being clogged when the ethylene glycol slurry is added. There is no particular lower limit to the viscosity, but the viscosity of the ethylene glycol slurry having the above-mentioned preferred organic crosslinked polymer particle concentration is usually 50 mPa·s or more. The viscosity here is a value measured by the method described in the Examples section below.

[0032] [Method of producing polyethylene terephthalate and polyethylene terephthalate film] The method for producing polyethylene terephthalate of the present invention can be carried out in a conventional manner except that the ethylene glycol slurry of the present invention is added in an optional step during the production of polyethylene terephthalate. The polyethylene terephthalate obtained by this method can be molded into a film in a conventional manner to obtain a polyethylene terephthalate film. The ethylene glycol slurry of the present invention can be used not only for the production of polyethylene terephthalate, but also for the production of various polyesters such as polyethylene naphthalate and various polyester films. EXAMPLES

[0033] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples as long as it does not depart from the gist of the present invention.

[0034] [Measurement and evaluation method] The organic crosslinked polymer particles used and the ethylene glycol slurries produced in the following Examples and Comparative Examples were measured and evaluated by the following measurement methods.

[0035] <Measurement of particle size distribution of crosslinked polymethyl methacrylate particles> Approximately 3 g of the sample was weighed out, and approximately 0.06 g of white carbon (hydrated silicate) was added to it. Using disposable polyethylene gloves, the sample was thoroughly covered on the palm of the hand to remove any moisture adhering to the surface of the sample. Next, the sample dusted with white carbon was placed on the top of a JIS standard sieve (850μm, 710μm, 500μm, 300μm, 250μm, 212μm) that was stacked in a sonic vibration type automatic sieving particle size distribution measuring instrument (product name: Robot Sifter RPS-85, manufactured by Seishin Enterprise Co., Ltd.). Next, the operating conditions of the robot sifter were set to an amplitude intensity of 7 to 9, and the sample was sieved for 5 minutes (alternating between operation and rest at 1 second intervals). The mass of the particles on each sieve that was sieved was automatically measured. Since the particle size of the white carbon is 212μm or less, it does not remain on the sieve. The particle size distribution of 250 to 850μm was calculated by dividing the sum of the particle masses remaining on each of the five sieves excluding 212μm in the sieve by the mass of the particles put in.

[0036] <Measurement of the volume average particle size of organic crosslinked polymer particles in ethylene glycol slurry> The volume average particle size was measured using a laser diffraction particle size distribution analyzer (product name: SALD-7500, manufactured by Shimadzu Corporation).

[0037] <Measurement of Viscosity of Ethylene Glycol Slurry> The viscosity was measured using a Brookfield viscometer (product name: TV-03F, manufactured by Rion Co., Ltd.) The measurement temperature was set at 30°C.

[0038] [Production of crosslinked polymethyl methacrylate particles] 3.2 parts by weight of potassium persulfate as a water-soluble polymerization initiator and 0.15 parts by weight of sodium lauryl sulfate as a dispersion stabilizer were added to 1500 parts by weight of demineralized water and dissolved uniformly, and then a mixed solution of 63 parts by weight of methyl methacrylate and 37 parts by weight of divinylbenzene was added. The polymerization reaction was carried out at 70°C for 24 hours while stirring under a nitrogen gas atmosphere. The obtained particles were observed under an electron microscope and were found to be almost spherical. The slurry after the polymerization reaction was spray-dried to obtain powdery crosslinked polymethyl methacrylate particles. When the particle size distribution of the obtained particles was measured, 90 mass % or more was 250 to 850 μm.

[0039] [Example 1] The crosslinked polymethyl methacrylate particles obtained above were dry-pulverized using a dry pulverizer (product name: Ultramizer ASK-2 type, manufactured by Fuji Paudal Co., Ltd.) to obtain irregular crosslinked polymethyl methacrylate particles having an average particle size of 2.0 μm. Next, 89.5 parts by mass of ethylene glycol, 0.5 parts by mass of anionic polymer surfactant (special ammonium polycarboxylate, product name: DKS Discoat N-14, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), and 15 ppm by mass of aspartic acid were placed in a container relative to 100 parts by mass of the obtained ethylene glycol slurry, and 10 parts by mass of dry-ground crosslinked polymethyl methacrylate particles were added and mixed with a stirrer to obtain an ethylene glycol slurry of crosslinked polymethyl methacrylate particles.

[0040] Next, this ethylene glycol slurry was subjected to a wet-pulverization process using a horizontal continuous wet medium stirring mill (product name: Dyno Mill, manufactured by Shinmaru Enterprises) so that the average particle size of the cross-linked methyl methacrylate particles was 0.8 μm, and then centrifuged using a cylindrical centrifuge (product name: ASM160, manufactured by Tomoe Engineering Co., Ltd.) and filtered using a cartridge filter (product name: SL-150, manufactured by Roki Techno Co., Ltd.) to obtain an ethylene glycol slurry of cross-linked methyl methacrylate particles of Example 1. The average particle size of the crosslinked polymethyl methacrylate particles in the ethylene glycol slurry was 0.8 μm, and the particle concentration was 10% by mass. The viscosity of the ethylene glycol slurry was measured immediately after its preparation and after it was stored at 60° C. for one week. The results are shown in Table 1. As shown in Table 1, the viscosity of the slurry after storage at 60°C for one week was 70 mPa·s, and no significant increase in viscosity was observed compared to immediately after the slurry preparation.

[0041] [Comparative Example 1] An ethylene glycol slurry of crosslinked polymethyl methacrylate particles was obtained in the same manner as in Example 1, except that aspartic acid was not added. The average particle size of the crosslinked polymethyl methacrylate particles in the ethylene glycol slurry was 0.8 μm, and the particle concentration was 10% by mass. The viscosity of the ethylene glycol slurry was measured immediately after its preparation and after it was stored at 60° C. for one week. The results are shown in Table 1. As shown in Table 1, after one week of storage at 60°C, the viscosity of the slurry increased to 190 mPa·s, causing pipe blockage when it was added to the polyester manufacturing process.

[0042] [Table 1] [Industrial Applicability]

[0043] According to the present invention, it is possible to provide an ethylene glycol slurry containing organic crosslinked polymer particles, which has excellent storage stability and suppresses an increase in viscosity during storage at high temperatures. Using this ethylene glycol slurry containing organic crosslinked polymer particles, it is possible to produce polyethylene terephthalate and polyethylene terephthalate films which contain organic crosslinked polymer particles and have a low friction coefficient and excellent wear properties with good workability.

Claims

1. 1. An ethylene glycol slurry comprising organic crosslinked polymer particles, a surfactant, aspartic acid and ethylene glycol, The organic crosslinked polymer particles have a volume average particle size of 0.01 μm or more and 3 μm or less, and the concentration (content) of aspartic acid in the ethylene glycol slurry is 1 ppm by mass or more and 100 ppm by mass or less.

2. A method for producing polyethylene terephthalate, comprising the step of adding the ethylene glycol slurry according to claim 1.

3. A method for producing a polyethylene terephthalate film, comprising molding the polyethylene terephthalate produced by the method for producing polyethylene terephthalate according to claim 2.

Citation Information

Patent Citations

  • Emulsified composition

    JP1987215510A

  • Polyester composition containing bathylitic calcium carbonate

    JP1992031456A

  • Polyethylene terephthalate and method for producing the same

    JP2006096840A

  • Polyester film, and method for producing polyester resin composition

    JP2014098136A

  • Polyester resin composition and its manufacturing method, and polyester film

    JP2014118493A